Beyond checkpoint inhibition: PD-1 cis-targeting of an IL-2Rβγ-biased interleukin-2 variant as a novel approach to build on checkpoint inhibition - Laura Codarri Deak; Masao Hashimoto; Pablo Umaña; Christian Klein (OncoImmunology)
The immunocytokine PD1-IL2v was designed to overcome liabilities and improve efficacy of IL-2 therapies. PD1-IL2v preferentially targets PD-1+ T-cells and acts on antigen-specific stem-like PD-1+ TCF-1+ CD8+ T-cells expanding and differentiating them towards better effectors resulting in superior efficacy in LCMV chronic infection and tumor models compared to checkpoint inhibition.